CONFLICT AND COOPERATION IN FOREST GOVERNANCE: A CASE STUDY - Dara, Ravi; Sothy, Chak; Sok, Vanna (Yayasan Adra Karima Hubbi, 2025)
Forest governance is a complex domain where conflict and cooperation often intersect, shaping the management and sustainability of forest resources. This research investigates the dynamics of conflict and cooperation in forest governance, exploring the interplay between stakeholders at various levels of decision-making. The study examines a specific case to understand the underlying factors that foster both collaboration and conflict within the governance framework. The aim of this study is to analyze the key factors contributing to both conflict and cooperation among stakeholders involved in forest governance and to assess the impacts of these interactions on the management of forest resources. By focusing on a case study, the research identifies critical patterns of behavior and decision-making processes. This research adopts a qualitative approach, utilizing in-depth interviews, field observations, and document analysis to gather comprehensive data. Stakeholders including local communities, government agencies, and environmental organizations were engaged to provide diverse perspectives on the governance processes. The findings indicate that while conflict often arises due to competing interests, cooperation is significantly enhanced through transparent communication, shared goals, and the active participation of all stakeholders. The case study reveals that collaborative efforts can lead to more sustainable forest management practices, but only when conflicts are effectively managed and resolved. In conclusion, forest governance requires a balanced approach that promotes cooperation while addressing conflicts. Effective strategies for conflict resolution and stakeholder engagement are essential for the sustainable management of forest resources.